Causal insights into the school-family-research integrated health promotion program for overweight and obesity: the independent role of moderate-to-vigorous physical activity in body fat reduction, undermined by psychological factors - Zhang, Xuehui; Pan, Xiang; Liu, Bing; Gao, Yibo; Jiang, Lupei; Chen, Xiaoxiao; Zhao, Deqiang; Wang, Yibei; Hu, Haixia; Zhao, Xueli; Lu, Jiahui; Suzuki, Koya; et al. (Frontiers in Nutrition, 2025)
IntroductionThis study implements the School-Family-Research Integrated Health Promotion Program for Overweight and Obesity (SFR-OO), which combines exercise and dietary interventions to combat adolescent obesity. It aims to enhance body composition, exercise motivation, SE, and physical fitness. By using a cross-lagged model, the study will explore causal relationships between self-esteem (SE), exercise self-efficacy (ESE), physical activity, and body composition.MethodsNinety-eight adolescents were randomly assigned to either the intervention group or the control group. The intervention group received the SFR-OO intervention for 12 weeks. Assessments included physical fitness tests, body composition, and psychological indicators.ResultsWhile both groups showed a time effect (p < 0.001), the intervention resulted in a significant decrease in body fat percentage (BFP) compared to the control group (p < 0.001, p < 0.038). Improvements were greater for knee push-ups, standing long jump, 4 x 10 meters round trip run and supine trunk raise time as well as psychometric measures (p < 0.001). In the intervention group, higher baseline MVPA significantly predicted greater reductions in BFP at 12 weeks (β = −0.169), whereas no such predictive relationship was found in the control group.DiscussionThe 12-week SFR-OO effectively enhanced adolescents’ body composition, physical fitness, and psychological outcomes. However, SE and ESE did not significantly predict MVPA or BFP. MVPA modestly predicted reduced BFP only within the intervention group, suggesting a context-dependent effect. This study was registered with ClinicalTrials.gov under the registration number NCT06524908.